2021
DOI: 10.22317/jcms.v7i3.970
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with poor glycemic control in patients with type two Diabetes mellitus in Zakho city

Abstract: Diabetes Mellitus (DM) is a chronic condition caused by relative lack of insulin due to impaired insulin secretion or insulin resistance. The aim of this study was to investigate the prevalence of poor glycemic control in Zakho city and to explore the modifiable risk factors that may help controlling the disease. Materials and Methods We recruited patients with known history of diabetes receiving oral anti-diabetic medications. Those patients were registered in Zakho Diabetes center with regular visits. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In this study, we found that male gender was associated with higher level of misconceptions. Our results support a previously conducted research in the Kurdistan region that found male patients to have a higher level of poor glycaemic control [22]. Individuals may not make the right decision when it comes to DM management if they have a high level of myths about the disease [23,24].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we found that male gender was associated with higher level of misconceptions. Our results support a previously conducted research in the Kurdistan region that found male patients to have a higher level of poor glycaemic control [22]. Individuals may not make the right decision when it comes to DM management if they have a high level of myths about the disease [23,24].…”
Section: Discussionsupporting
confidence: 87%